Semi-synthesis as a tool for broadening the health applications of bioactive olive secoiridoids: a critical review. Issue 3 (10th December 2020) - Oliverio, Manuela; Nardi, Monica; Di Gioia, Maria Luisa; Costanzo, Paola; Bonacci, Sonia; Mancuso, Stefano; Procopio, Antonio
Abstract : Semi-synthesis is an effective strategy to obtain both natural and synthetic analogues of the olive secoiridoids, starting from easy accessible natural compounds. Abstract : Covering: 2005 up to 2020 Olive bioactive secoiridoids are recognized as natural antioxidants with multiple beneficial effects on human health. Nevertheless, the study of their biological activity has also disclosed some critical aspects associated with their application. Firstly, only a few of them can be extracted in large amounts from their natural matrix, namely olive leaves, drupes, oil and olive mill wastewater. Secondly, their application as preventive agents and drugs is limited by their low membrane permeability. Thirdly, the study of their biological fate after administration is complicated by the absence of pure analytical standards. Accordingly, efficient synthetic methods to obtain natural and non-natural bioactive phenol derivatives have been developed. Among them, semi-synthetic protocols represent efficient and economical alternatives to total synthesis, combining efficient extraction protocols with efficient catalytic conversions to achieve reasonable amounts of active molecules. The aim of this review is to summarize the semi-synthetic protocols published in the last fifteen years, covering 2005 up to 2020, which can produce natural olive bioactive phenols scarcely available by extractive procedures, and new biophenol derivatives with enhanced biological activity. Moreover, the semi-synthetic protocols to produce olive bioactive phenol derivatives as analytical standards are also discussed. A critical analysis of the advantages offered by semi-synthesis compared to classical extraction methods or total synthesis protocols is also performed.